면역 저하 모델에서 블루베리 효모 발효 분말의 면역 조절 기능 평가 - 정도연(Do Youn Jeong); 양희종(Hee Jong Yang); 정수지(Su Ji Jeong); 신동엽(Dong Yeop Shin); 이학용(Hak Yong Lee); 박영미(Young Mi Park) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2020)
블루베리 효모 발효 분말은 세포주를 이용한 시험에서 cyclophosphamide에 의한 비장세포의 생존율 저하를 감소시키고, 자연살해세포의 활성과 cytokine의 생성량을 효과적으로 증가시키는 것으로 나타났다. 면역 저하 동물 모델에서 블루베리 효모 발효 분말은 일반 혈액학적 분석 및 cytokine 분석에서 대조군과 비교하여 블루베리 효모 발효 분말을 투여한 시험군은 면역 관련 인자들의 혈중 수치가 높게 나타났는데, 이 중 BYFP 300 시험군의 경우 대부분의 바이오마커에서 양성 대조군인 헤모힘보다도 높은 수준을 보이는 것으로 확인되었다. 조직학적 분석에서 비장 조직은 대조군에서 관찰되던 백색수질의 붕괴와 적색수질에서의 세포 응축현상은 블루베리 발효 추출물을 투여한 시험군에서 점차 호전되는 경향을 보였고, 자연살해세포 활성능 분석에서 블루베리 효모 발효 분말을 투여한 시험군 모두에서 대조군에 비해 활성이 유의하게 증가한 것으로 나타났다. 따라서 본 연구의 블루베리 효모 발효 분말은 천연물 유래 면역 증강제(immunostimulator)로서의 역할이 가능할 것으로 기대되며, 추후 제형 및 발효 공정의 개선과 품질의 향상 연구를 통해 면역질환으로 고통받는 환자들에게 좋은 보조제가 될 수 있을 것으로 사료된다. This study aimed to examine the immunomodulatory effects of blueberry yeast fermented powder (BYFP). BYFP is reported to reduce the cytotoxicity induced by cyclophosphamide, and increase the activity of natural killer cells and production of cytokine in splenocytes. An in vivo experimental assay was performed to evaluate the immunomodulatory effects of BYFP in cyclophosphamide induced immunosuppressed rats. Complete blood cell count and cytokine analysis showed that BYFP administered groups had higher levels of blood immune related factors as compared to the control group, and levels of most biomarkers in the BYFP 300 group were determined to be higher than the positive control group. Histological analysis revealed that the spleen tissues in the BYFP administered group had a tendency to decrease the white pulp collapse and the red pulp cell condensation observed in the control group. All test groups administered BYFP showed significantly increased natural killer cell activity compared to the control group. Taken together, our results indicate that BYFP is a potential candidate for immunostimulation, and the improvement and quality of the blueberry fermentation process may generate a health care product for patients suffering from autoimmune diseases. KCI Citation Count: 3